Welding failure examination on a fuel tank of a 650 cm3 motorbike. (October 2017) - Medrea, C.; Loukopoulos, A.; Chicinaş, I.; Papageorgiou, D.G.
Abstract: The failure of a motorbike fuel tank was investigated. Leakage of fuel was detected on the stabilizing subassembly at the front side of the base. The main container was replaced. The new container ended up leaking as well after only four months of use, proving that the failure was not a random incident. The study comprises visual examination, non-destructive testing by penetrant liquids, microhardness measurements and chemical analysis. Welded samples of the leakage area were investigated from macroscopic and microscopic perspective. The microstructure was analyzed by optical and scanning electron microscopy. Welding defects were found on the failure area. Most of them could be associated to inappropriate welding parameters. Hairline cracks were detected on resistance spot welding points. The cracks originated approximately at the center of the weld nugget, propagated through the weld zone, pierced the welding interface and reached the opposite sheet surface. Findings indicated interfacial failure mode. Poor welding process is considered the main cause of the failure and the specific sequence should be improved. Detailed practice recommendations and rigorous inspection are required to assure tank integrity. The tank tightness is of pivotal importance for the safe operation of the engine, the safety of passengers and protection of the environment. Highlights: A study on the failure of a motorbike tank at the front side of its base due to leakage of fuel. Poor welding is assumed as the main reason of failure. Recommendations are given in order to avoid a similar case in the future.